The Influence of Work Discipline on Public Service Productivity: A Study of the Regional Disaster Management Agency of Pagar Alam City - Yeyen Saputri; Elvera Elvera; Laili Dimyati (The Future of Education Journal, 2026)
This study aims to determine the effect of work discipline on the productivity of public services at the Regional Disaster Management Agency (BPBD) of Pagar Alam City. The research employed a quantitative method with an associative approach. The population consisted of 79 employees of the Regional Disaster Management Agency (BPBD) of Pagar Alam City, and the entire population was used as the research sample through a saturated sampling technique. Data were collected through observation, interviews, literature study, and questionnaires. The data were analyzed using validity tests, reliability tests, normality tests, simple linear regression analysis, the coefficient of determination, and the t-test with the assistance of SPSS software. The results of the study indicate that the regression equation obtained is Y = 0.364 + 0.688X, which means that work discipline has a positive relationship with public service productivity. The coefficient of determination (R Square) is 0.464, indicating that work discipline explains 46.4% of the variation in public service productivity, while the remaining 53.6% is influenced by other factors not examined in this study. The regression test results show that work discipline has a positive effect on public service productivity. This study implies that improving employees’ work discipline can contribute to enhancing the productivity of public services within the Regional Disaster Management Agency (BPBD) of Pagar Alam City.